Magnetic interaction between Q(A)(-center dot) and the triplet state of the primary donor in modified reaction centers of the photosynthetic bacterium Rhodobacter sphaeroides R26 - Bosch, M; Gast, P; Franken, E; Zwanenburg, G; Hore, P; Hoff, A (1996)
The interaction between the reduced primary acceptor quinone (Q(A)-.), and the triplet state of the primary donor 3D is investigated with time-resolved continuous-wave EPR. The trough at high-field in the Q(A)-. electron-spin polarized X-band EPR-spectrum at early delay times after the laser flash [De Groot et al. (1985) Biochim. Biophys. Acta 808, 13-20] is studied as a function of temperature and of the delay, in zinc-reconstituted reaction centers, with and without carotenoid. In all cases investigated a decrease in 3D concentration is accompanied by a simultaneous attenuation of the high-field trough in the Q(A)-. EPR spectrum. These observations confirm the hypothesis that the line-shape of Q(A)-. at short delay times is influenced by a magnetic interaction with 3D. The line-shape of the Q(A)-. electron-spin polarized EPR spectrum directly after the laser flash, could be very well simulated using an extension of the model of Here et al. [Hore, P.J. et al. (1993) Biochim. Biophys. Acta 1141, 221-230], with dipolar coupling between Q(A)-. and 3D of -0.125 mT.